2020
DOI: 10.1029/2020wr027307
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Historical Precipitation Into Evaporation and Runoff Based on Hydrologic Dynamics Identified With Recent SMAP Satellite Measurements

Abstract: Microwave brightness temperature observations from the NASA Soil Moisture Active Passive (SMAP) mission and gauge-based precipitation data over the United States are used to reconstruct the soil water loss function and then historical (1979-2019) hydrological fluxes in the form of evapotranspiration (ET) and drainage (D) are quantified. Over the period of study, with the exception of snowy and hyper-arid regions, we observe a correlation of R 2 > 0.6 between SMAP-precipitation derived drainage estimates and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…While soil moisture in the unsaturated zone stores only 0.005% of Earth's water by volume (Bras, 1990), its position at the interface of the land and the atmosphere is of high value for understanding these global cycles (Koster & Suarez, 2001; McColl et al., 2017). As such, satellite‐based soil moisture estimates are increasingly being used in studies of land‐atmosphere interactions, numerical weather prediction, plant function and stress, and land surface response to climate change (Akbar et al., 2020; Dong et al., 2020; Feldman, Akbar, & Entekhabi, 2018; Feldman et al., 2022; Konings et al., 2017; Purdy et al., 2018; Santanello et al., 2019; Short Gianotti et al., 2020; Taylor et al., 2012; Tuttle & Salvucci, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While soil moisture in the unsaturated zone stores only 0.005% of Earth's water by volume (Bras, 1990), its position at the interface of the land and the atmosphere is of high value for understanding these global cycles (Koster & Suarez, 2001; McColl et al., 2017). As such, satellite‐based soil moisture estimates are increasingly being used in studies of land‐atmosphere interactions, numerical weather prediction, plant function and stress, and land surface response to climate change (Akbar et al., 2020; Dong et al., 2020; Feldman, Akbar, & Entekhabi, 2018; Feldman et al., 2022; Konings et al., 2017; Purdy et al., 2018; Santanello et al., 2019; Short Gianotti et al., 2020; Taylor et al., 2012; Tuttle & Salvucci, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hrachowitz et al (2014) demonstrated that an uncalibrated but constrained complex model yielded levels of model performance and uncertainty similar to those of a calibrated but unconstrained standard lumped model. As various types of remotely sensed data emerge (e.g., soil water content and water levels) and hydrological information and knowledge accumulate, soft data is expected to be used to a greater extent to complement hard calibration in hydrological analysis (Akbar et al, 2020;Huang et al, 2020;Mao et al, 2020). Advanced uncertainty and sensitivity analysis methods such as a global sensitivity analysis (Razavi et al, 2021;Sheikholeslami et al, 2019) may help reduce the parameter spaces by identifying a dominant group of parameters that significantly contribute to variability in model outputs (see Figures S2 and S3 in Supporting Information S1 for more information).…”
Section: Discussionmentioning
confidence: 99%
“…The great importance of the water balance equation, which posits that precipitation is equal to runoff plus evaporation and was first suggested by A. Penck in 1896 [12], is well known in hydrological sciences. The partition of precipitation into evapotranspiration and runoff at the land surface plays an important role in the Earth's hydrology and climate system [25,26]. Common precipitation abnormal phenomena are droughts and floods.…”
Section: "Down To Top" Surrounding Assessment Methodologymentioning
confidence: 99%